Not just a drop in the bucket: Measuring women’s empowerment in water, sanitation, and hygiene - Myers, Emily; Baek, Yuna; Ramani, Gayathri V.; Heckert, Jessica (International Food Policy Research Institute, 2022)
Given the lack of consensus around how to measure empowerment in WASH, mapping existing indicators to two frameworks frequently used in the empowerment literature illustrates knowledge gaps. We identified 290 gender-sensitive indicators across nine WASH themes that were mapped to the Reach-Benefit-Empower and Resources-Agency-Achievements frameworks. Most indicators measure “Benefit” and/or “Resources.” Existing gender-sensitive indicators capturing empowerment and agency in WASH are lacking; only 10.3% of indicators capture “Empower” and 24.8% of indicators capture “Agency.”